Students' experiences of collaborative creation through songcrafting in primary school: Supporting creative agency in 'school music' programmes1. Issue 3 (15th July 2016) - Muhonen, Sari
Abstract : The study reported in this article investigates students' experiences (n=41) of their primary school songcrafting, examining the potential to support creative agency within school music education programmes. Songcrafting refers to a collaborative composing practice in which everyone is considered to be a capable creator of melodies and lyrics, and where negotiation, collaboration, and openness to the situation are essential. Through semi-structured individual interviews with students who had experienced songcrafting in the past, analysed with qualitative methods, it was found that the students' narration of songcrafting included meanings related to general agency, creative agency, musical participation within the classroom community, and documented and shared collaborative musical products, or 'oeuvres'. The results of this study illustrate the various often unforeseeable meanings produced through participation in collaborative musical activities. Furthermore, they highlight the potential to enrich meaningful teaching practices and pedagogy through the examination of students' experiences, and exploring the potentials in narrating one's musical stories. These findings suggest that music education practices could benefit from the inclusion of a broader range of opportunities for the students to create their own music, and the sensitive facilitation of collaborative music creation processes.